C1q and central nervous system disorders - Zhang, Wenjie; Chen, Yuan; Pei, Hui (Frontiers in Immunology, 2023)
C1q is a crucial component of the complement system, which is activated through the classical pathway to perform non-specific immune functions, serving as the first line of defense against pathogens. C1q can also bind to specific receptors to carry out immune and other functions, playing a vital role in maintaining immune homeostasis and normal physiological functions. In the developing central nervous system (CNS), C1q functions in synapse formation and pruning, serving as a key player in the development and homeostasis of neuronal networks in the CNS. C1q has a close relationship with microglia and astrocytes, and under their influence, C1q may contribute to the development of CNS disorders. Furthermore, C1q can also have independent effects on neurological disorders, producing either beneficial or detrimental outcomes. Most of the evidence for these functions comes from animal models, with some also from human specimen studies. C1q is now emerging as a promising target for the treatment of a variety of diseases, and clinical trials are already underway for CNS disorders. This article highlights the role of C1q in CNS diseases, offering new directions for the diagnosis and treatment of these conditions.